Infâncias em Educação Infantil Different kinds of childhood in early childhood education - Anete Abramowicz; Diana Levcovitz; Tatiane Cosentino Rodrigues (Pro-Posições, 2009)
Este artigo, por sua natureza teórica, trabalha com noções tais como infâncias, crianças, multidão e experiência, no intuito de pensar uma educação cujas práticas educativas possibilitem o exercício da infância. O artigo refaz um caminho no qual a infância e a criança são percebidas "em sua dimensão singular", de modo a recuperar, no fim do percurso, o caráter plural que as noções de criança e infância encerram. O referencial teórico parte de Deleuze, Guattari, Agamben, entre outros autores, e busca colocar a infância numa temporalidade múltipla, em detrimento da temporalidade fundada em visões da história e da psicologia, que privilegiam etapas e sucessões cronológicas. Ao afirmarmos a infância como atravessada pela experiência, pela inventividade e pelo desarazoamento, propomos pensar uma educação na direção da multidão. This article, in its theoretical nature, discusses notions such as childhood, children, multitude and experience, in order to consider a kind of early childhood education in which educational routine enables the practice of childhood to happen. The article rebuilds a path on which childhood and children are perceived according to a single particular notion. Towards the ending of the analysis, the plural character involved in the notions of child and childhood is considered.The theoretical framework for the analysis was based on the propositions of Deleuze, Guattari and Agamben, among others. Their views place childhood in a multiple temporality rather than in a single temporality which is determined by historical and psychological perspectives both based on chronological and succession levels. By stating that childhood is crossed by experiences, inventiveness and unreasonableness, our proposal is about thinking of a different kind of education, which leans towards the multitude.